Decavavanadate (V10 O6-28) and oxovanadates: oxometalates with many biological activities - Aureliano, M. (2012)
The decameric vanadate species V10O6 28 , also referred to as decavanadate, impact proteins, lipid structures and cellular function, and show some effects in vivo on oxidative stress processes and other biological properties. The mode of action of decavanadate in many biochemical systems depends, at least in part, on the charge and size of the species and in some cases competes with the simpler oxovanadate species. The orange decavanadate that contains 10 vanadium atoms is a stable species for several days at neutral pH, but at higher pH immediately converts to the structurally and functionally distinct lower oxovanadates such as the monomer, dimer or tetramer. Although the biological effects of vanadium are generally assumed to derive from monomeric vanadate or the vanadyl cation, we show in this review that not all effects can be attributed to these simple oxovanadate forms. This topic has not previously been reviewed although background information is available [D.C. Crans, Comments Inorg. Chem. 16 (1994) 35–76; M. Aureliano (Ed.), Vanadium Biochemistry, Research Signpost Publs., Kerala, India, 2007]. In addition to pumps, channels and metabotropic receptors, lipid structures represent potential biological targets for decavanadate and some examples have been reported. Decavanadate interact with enzymes, polyphosphate, nucleotide and inositol 3-phosphate binding sites in the substrate domain or in an allosteric site, in a complex manner. In mitochondria, where vanadium was shown to accumulate following decavanadate in vivo administration, nM concentration of decavanadate induces membrane depolarization in addition to inhibiting oxygen consumption, suggesting that mitochondria may be potential targets for decameric toxicity. In vivo effects of decavanadate in piscine models demonstrated that antioxidant stress markers, lipid peroxidation and vanadium subcellular distribution is dependent upon whether or not the solutions administered contain decavanadate. The present review summarizes the reports on biological effects of decavanadate and highlights the importance of considering decavanadate in evaluations of the biological effects of vanadium.